Efforts to Improve Numeracy Literacy Culture and History Learning Outcomes with the Problem-Based Learning Method for Class XII IPS 2 at SMAN 6 Metro - Sumiati Sumiati (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to describe problem-based learning methods as an effort to improve numeracy literacy and history learning outcomes. Data analysis in this study used data analysis obtained through three stages, namely: (1) data reduction, (2) data presentation, and (3) drawing conclusions (data verification). Source of data obtained from primary data and secondary data. Tools and data collection with test and non test techniques. Results and discussion: the numeracy literacy of class XII IPS 2 students of SMAN 6 Metro can be explained as follows: pre-cycle 58%, cycle I became 72%, cycle II increased to 85%, and cycle III decreased to 84%. While learning outcomes increase, this is from the average pre-cycle results of 52.22%, and cycle I become 70.37%. Cycle II became 78.51, cycle III increased to 85.92%. Learning completeness in pre-cycle is still 0, in cycle I there is 40.74%, cycle II is 81.48%, and cycle III is 100%.